KOMPETENSI KOMUNIKASI ANTARBUDAYA SEBAGAI SARANA MEMBANGUN KERUKUNAN DI MASYARAKAT - A, Gun Sukirman (Jurnal Insani, 2016)
Competency of intercultural communication is very important, especially in Indonesia which consists of diverse ethnicities, races, and religions. Frequently conflicts between ethnics, races, and religions took place.This study described problem how is competency of intercultural communication from Catholic Church Santo Servatius at Kampung Sawah, Jati Melati, Bekasi City to build relationship between Catholic congregation and local community, what is competency of intercultural communication should be done by Catholic Church Santo Servatius Kampung Sawah Bekasi and how to build a communication intercultural pattern by Catholic Church Servatius Kampung Sawah Kota Bekasi. The goal is to know about competency of intercultural communication and to determine the pattern of communication intercultural by Catholic Church Santo Servatius Kampung Sawah. The theory associated with this research is communication intercultural theory and symbolic interaction. The subject of this study is congregation of Catholic Church Santo Servatius Kampung Sawah Bekasi. The subject used a qualitatif research with a case study. Data collection technique is using observation, deeply interview and documentation.The fact results was found in the field is competency of intercultural communication of Dewan Paroki Catholic Church of Santo Servatius Kampung Sawah to build relations between the congregation in church and local communities Kampung Sawah through a cultural approach and developing cultural wisdom Kampung Sawah with inculturation culture of Kampung Sawah Betawi, and how to build communication with others religions and ethnics with actively. So the congregation in church and the local community can living together in harmony and peace situation. Intercultural communication through local cultural approach is very effective in creating harmony between religions.